Adjustment Under a Currency Peg : Estonia, Latvia and Lithuania During the Global Financial Crisis 2008-09 - Purfield, Catriona (IMF Working Papers; Working Paper ;, 2010)
The paper traces the Baltics' adjustment strategy during the 2008-09 global financial crisis. The abrupt end to the externally-financed domestic demand boom triggered a severe output collapse, bringing per capita income levels back to 2005/06 levels. In response to this shock, the Baltics undertook an internal devaluation that relied on unprecedented fiscal and nominal wage adjustment, steps to preserve financial sector stability as well as complementary efforts to facilitate voluntary private debt restructuring. One-and-half years on, the strategy is making good progress but not yet complete. Confidence in the exchange rate was maintained, the banking system was supported by its parent banks, external imbalances and inflation have largely disappeared, competitiveness is improving, and fiscal deficits are gradually being brought back towards pre-crisis levels. However, amid record levels of unemployment, further reforms are needed to foster a return to more balanced growth, fiscal sustainability, and a healthier banking system.